Aluminium‐Mediated Carbon Dioxide Reduction by an Isolated Monoalumoxane Anion. Issue 50 (24th October 2019) - Anker, Mathew D.; Coles, Martyn P.
Abstract: The deoxygenative conversion of carbon dioxide to carbon monoxide is promoted by the aluminyl anion [Al(NON Ar )] − (NON Ar =[O(SiMe2 NAr)2 ] 2−, Ar=2, 6‐ i Pr2 C6 H3 ). The reaction proceeds via the isolable monoalumoxane anion [Al(NON Ar )(O)] −, containing a terminal aluminum‐oxygen bond. This species reacts with a second equivalent of carbon dioxide to afford the carbonate [Al(NON Ar )(CO3 )] −, and with nitrous oxide to generate the hyponitrite anion, [Al(NON Ar )(κ 2 O, O′ ‐N2 O2 )] − . Abstract : Suck it up ! An isolated monoalumoxane anion reacts with the greenhouse gases CO2 and N2 O to generate potentially useful chemical compounds.